Turbidity Removal Efficiency of Tannin Based Flocculants Derived from Different Agricultural Waste - Hoang Oanh, Le Thi; Minh Loan, Luu; Van Hao, Nguyen; Thi Thuy, Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1SDO - 10.25073/2588-1094/vnuees.5205, 2024)
Tannin-based flocculants have been investigated, produced, and commercialized as a promising product in water supply and wastewater treatment. This study compared turbidity removal efficiency of tannin-based flocculants produced from different agricultural waste. Tannin was extracted using ultrasonic method (ethanol 50%, 2 h, 500 kHz) and modified according to Mannich reaction using HCHO and NH 4 Cl. The coagulation and flocculation efficiencies were determined using Jar-tests on artificial wastewater with initial turbidity of 200 NTU. The results showed that at pH 7 and alum dosage of 5 ppm, turbidity removal efficiency of flocculants derived from longan pericarp, mimosa bark, green tea waste, and green banana peel were 93%, 92.7%, 92%, and 89.8%, respectively; corresponding to flocculant dosages of 10 ppm, 12 ppm, 8 ppm and 8 ppm. Production efficiency for green tea waste (9.4%), mimosa bark (7.1%), longan pericarp (4.6%) were much higher than that for green banana peel (0.5%). Based on the turbidity removal and production efficiencies as well as the optimal dosages of tannin-based flocculants, green tea waste was found to be the most potential material of all four agricultural waste to produce tannin-based flocculants.